2002
DOI: 10.1191/1352458502ms816oa
|View full text |Cite
|
Sign up to set email alerts
|

Disease severity in Danish multiple sclerosis patients evaluated by MRI and three genetic markers (HLA-DRB1*1501, CCR5 deletion mutation, apolipoprotein E)

Abstract: As the understanding of the autoimmune inflammatory response in multiple sclerosis (MS) expands, polymorphic genes involved in this process become possible candidates that may determine the severity of disease. Therefore, three candidate genes DRB1*1501, CCR5 and apolipoprotein E (APOE) were examined in a population-based patient sample (n = 70) to assess an association between disease progression measured by clinical disability and MRI parameters. The total lesion area (TLA) on T2-weighted images was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
1
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 33 publications
(36 reference statements)
3
30
1
4
Order By: Relevance
“…Patients with the CCR5-∆32 allele showed a non-significant trend towards a small lesion burden (total lesion area/years duration), but the presence of this allele was not associated with a mild edSS/year duration. the data support the previous hypothesis of a modulation of severity in MS by the CCR5-∆32 genotype, which may result in less inflammation and tissue destruction (66). However, due the limited number of patients enrolled, weak associations between this polymorphism and disease variables cannot be excluded.…”
Section: Tnf-a Tnf-β and The Tnf Receptor Genessupporting
confidence: 87%
See 1 more Smart Citation
“…Patients with the CCR5-∆32 allele showed a non-significant trend towards a small lesion burden (total lesion area/years duration), but the presence of this allele was not associated with a mild edSS/year duration. the data support the previous hypothesis of a modulation of severity in MS by the CCR5-∆32 genotype, which may result in less inflammation and tissue destruction (66). However, due the limited number of patients enrolled, weak associations between this polymorphism and disease variables cannot be excluded.…”
Section: Tnf-a Tnf-β and The Tnf Receptor Genessupporting
confidence: 87%
“…the association between the apoe and mS progression measured by clinical disability and mri parameters was evaluated in a population-based patient sample (n=70). carriers of the apoe-ε4 alleles did not show a more severe disease progression, neither by edSS/years of duration nor by the total lesion area/years duration (66). although the study was carried out on a genetically homogeneous danish population, the limited number of mS patients enrolled could interfere with the results obtained and the association between this gene and disease variables could not be excluded.…”
Section: Apolipoprotein E Gene (Apoe)mentioning
confidence: 94%
“…21 Genetic studies indicate MS is likely to be a polygenic disorder, due to multiple gene associations. [22][23][24] Some of the genes reported to be associated with MS include interleukin, 25,26 CTLA4, 27 HLA-DRB1*1501, and apolipoprotein E. 28 Early- …”
mentioning
confidence: 99%
“…21 Genetic studies indicate MS is likely to be a polygenic disorder, due to multiple gene associations. [22][23][24] Some of the genes reported to be associated with MS include interleukin, 25,26 CTLA4, 27 HLA-DRB1*1501, and apolipoprotein E. 28 Early-published reports 29,30 of epidemiological studies of MS concluded that the disease was common in persons of Scandinavian descent: an ethnic group that exhibits a high prevalence of CCR5 ⌬32 mutation. Among the European white population there is a north to south gradient of prevalence of the CCR5 ⌬32 mutant allele, with the allelic frequencies highest in Scandinavia (16%) and lowest in Sardinia (4%), with a mean allelic frequency across the whole of Europe of 9.1%, where as this variant was found in only 1% in individuals of African origin, 0% in Asians, and 9.8% in Caucasians.…”
mentioning
confidence: 99%
“…Although homozygous individuals for CCR5-Δ32 were not protected from MS, heterozygosity for this deletion has been associated to prolonged diseasefree intervals and a delay in MS onset and with a lower risk of recurrent clinical disease activity (12). Results obtained in another study also confirm that the genotype CCR5-Δ32 could modulate the severity in MS, resulting in less inflammation and tissue destruction (33).…”
Section: Ccr5-δ32 Genetic Polymorphism Associated With Benign Clinicamentioning
confidence: 86%